1996
DOI: 10.1029/96eo00227
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric Experiment probes deep physical state of southeastern United States

Abstract: A combined continental‐oceanic magnetotelluric (MT) transect of the southern Appalachians orogenic belt has been completed that spans nearly 600 km on land and extends over 1000 km offshore beneath the Atlantic Ocean (Figure 1). The study is revealing the long‐term changes in the lithosphere that occur as active subduction regimes degenerate to fossil regimes, and tests the degree to which the latter are modified by subsequent extension. The electrical resistivity structure of active subduction has been examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Sénéchal et al (1996), for instance, through coupled shear wave splitting measurements and magnetotelluric soundings along a transect in the Canadian shield, retrieved similar directions of anisotropy from both datasets and, considering that the measured electrical anisotropy originates between 50 and 150 km, they concluded that the seismic anisotropy also originates from a well-defined fabric in the lithospheric upper mantle fabric. Similar preliminary results have been obtained in the Appalachians (Wannamaker et al, 1996) and the Pyrenees (Pous et al, 1995;M. Daignières, pers.…”
Section: Tectonic Fabric Of the Continental Lithospheric Mantlesupporting
confidence: 72%
See 1 more Smart Citation
“…Sénéchal et al (1996), for instance, through coupled shear wave splitting measurements and magnetotelluric soundings along a transect in the Canadian shield, retrieved similar directions of anisotropy from both datasets and, considering that the measured electrical anisotropy originates between 50 and 150 km, they concluded that the seismic anisotropy also originates from a well-defined fabric in the lithospheric upper mantle fabric. Similar preliminary results have been obtained in the Appalachians (Wannamaker et al, 1996) and the Pyrenees (Pous et al, 1995;M. Daignières, pers.…”
Section: Tectonic Fabric Of the Continental Lithospheric Mantlesupporting
confidence: 72%
“…Electrical anisotropy measurements in the Canadian shield (Sénéchal et al, 1996) and the eastern US (Wannamaker et al, 1996) show a very good agreement between the directions of conductivity anisotropy in the upper mantle and the crustal tectonic fabric, suggesting that the mantle and the crustal fabrics are similar.…”
Section: Rheology Of the Lithospherementioning
confidence: 82%
“…and one in the early-middle Paleozoic (Taconic), with final collision and plutonism in the Late Paleozoic (Alleghanian) (Hatcher, 1989;van Schmus et al, 1993;Rankin, 1994;Hibbard et al, 2002). Tectonic setting and problems, MT data collection, and basic response trends were discussed by Wannamaker et al (1996), and a 2D isotropic inversion model using just the sparser long period soundings was derived by Ogawa et al (1996). Merged wideband and long period data were inverted by Wannamaker et al (2004) and Wannamaker (2005).…”
Section: Fossil Transpressional Regimesmentioning
confidence: 98%
“…It is thus a fossil analogue to the current situation under the South Island of New Zealand, Figure 16. Three inversion cross sections derived from MT transect across southern Appalachians compressional orogenic belt (site map and data in Wannamaker et al, 1996). Top section is TM mode only, middle section is joint TM-TE phase-vertical H-field model, and bottom is TE impedance phase and vertical magnetic field with model adherence to the TM mode section.…”
Section: Fossil Transpressional Regimesmentioning
confidence: 99%
“…Anisotropic electrical conductivity in the lithospheric mantle with a fast conduction direction subparallel to the polarization of the fast split S-wave and to the tectonic trend has been proposed, for instance, beneath the Grenville front (Sénéchal et al, 1996), the Great Slave shear zone (Eaton et al, 2004), the Appalachians (Wannamaker et al, 1996), the Neoproterozoic belts of southeastern Brazil (Padilha et al, 2006), and the Variscan belt in central Germany (Gatzemeier and Moorkamp, 2005). In contrast, in the Kaapvaal lithospheric mantle, inferred fast conduction directions are oblique to the polarization of the fast split S-waves (Hamilton et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%